Electron tomography on III-Sb heterostructures on vicinal Si(001) substrates: Anti-phase boundaries as a sink for threading dislocations. (15th April 2017) - Niehle, Michael; Trampert, Achim; Rodriguez, Jean-Baptiste; Cerutti, Laurent; Tournié, Eric
Abstract: The three-dimensional arrangement of threading dislocations in a III-Sb based mid-infrared laser structure is studied by electron tomography (in a scanning transmission electron microscope). The stack of planar antimonide films which are grown by molecular beam epitaxy on vicinal Si(001) substrates, exhibits an inhomogeneous distribution of threading dislocations. A strong interaction of these line defects with planar defects is revealed. A significant number of dislocations appears to be trapped in anti-phase boundaries which are predominantly parallel to (110) lattice planes. Based on this finding, an explanation for the inhomogeneous distribution of dislocations is established. Graphical Abstract: